Study of Physical Quality of Complete Feed Pellet with Different Forages Source and Binders - Widiyastuti, T; Prayitno, CH; Munasik, Munasik (ANIMAL PRODUCTION, 2004)
The purpose of this study was to know the effect of utilization of various kinds of binders in the making of complete diet that was made of several species of forages that was viewed from its physical properties (hardness and durability).  There were two formulations of complete feed and four kinds of binders a pelleting machine was used in this study.  Factorially, based on Completely Randomized Design (CRD) was used with feed formulation (A) with two levels namely elephant grass and the leaves of leucaena (a1) and rice straw and peanut straw (a2) as the sources of forage as the first factor, and the kinds of binders (B) with 3 % levels of each binders.  Four levels of binders namely b0 (without binder), b1 (lignosulphonate), b2 (bentonite) and b3 (CMC) were as the second factor.  There were 3 replications in each treatment combination.  Based on the results of this study, it was conclude that the hardness of pellets of complete feed was affected by feed formulations based on different kinds of forage and pellets binders, but not for durability of the pellets.  The highest value of hardness was achieved by a1b1 formulation. (Animal Production 6(1): 43-48 (2004) Key Words: Hardness, Durability, Complete Feed Pellet